Strategi Peningkatan Mutu dan Keamanan Produk Olahan Melalui Pelatihan Good Manufacturing Practice (GMP) pada UKM Piyasan Nanggroe Kabupaten Aceh Utara - Khairisma; Fuadi; Puspitaningrum, Rani; Falahuddin; Juanda, Reza; Sinta, Irada; Khairani, Aulia Febri; Mirna; Ayu, Sari (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Community Engagement activities were conducted in Gampong Matang Meunye, Aceh Utara District, with a focus on the development of Micro, Small, and Medium Enterprises (MSMEs) represented by the UKM Piyasan Nanggroe group. This group possesses expertise in producing high-quality dried bananas, referred to as